-6(-8-7x)+5=-37-3x

Simple and best practice solution for -6(-8-7x)+5=-37-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(-8-7x)+5=-37-3x equation:


Simplifying
-6(-8 + -7x) + 5 = -37 + -3x
(-8 * -6 + -7x * -6) + 5 = -37 + -3x
(48 + 42x) + 5 = -37 + -3x

Reorder the terms:
48 + 5 + 42x = -37 + -3x

Combine like terms: 48 + 5 = 53
53 + 42x = -37 + -3x

Solving
53 + 42x = -37 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
53 + 42x + 3x = -37 + -3x + 3x

Combine like terms: 42x + 3x = 45x
53 + 45x = -37 + -3x + 3x

Combine like terms: -3x + 3x = 0
53 + 45x = -37 + 0
53 + 45x = -37

Add '-53' to each side of the equation.
53 + -53 + 45x = -37 + -53

Combine like terms: 53 + -53 = 0
0 + 45x = -37 + -53
45x = -37 + -53

Combine like terms: -37 + -53 = -90
45x = -90

Divide each side by '45'.
x = -2

Simplifying
x = -2

See similar equations:

| 3m+2n+5m+4n= | | 3t+1=6t-9 | | 1.1+-15x+3x=15x+-2+4 | | 4x=2(x+1)+3(x+1) | | z+2y=114x | | 2(4x-3)=-26+4x | | -3+9z+2-7z= | | 100x=5x-1 | | 11+4j=-5 | | -3(-6-8k)=18-3k | | 12r+54r= | | -6m+6=12 | | 66+20*x=300*86x | | x+4y=99 | | 19-0.6x=16.6 | | 3(2m+3)+9=5m+8 | | 2(x-9)+6=-12 | | -18n+5n=4(n-4) | | -22=-43 | | 6(x+2)+2x-4=8(x+2)+7 | | 12x^3-24x^2-111x+60=0 | | 1=a(0-b)(0-7.1) | | 4x+12=6x-22 | | 256x^3-x=0 | | 5(5x+3)-11=-9x+11-6x-19 | | 5x+4+57+64=180 | | 1890+1240y=9100 | | 3.5=a(x-0)(x-1.5) | | 5(5x+3)-11=-x+11-6x-19 | | 3.5=a(x-e)(x-7.1) | | 35c-25c= | | x/2+x/4=1/8 |

Equations solver categories